2015
DOI: 10.1155/2015/461625
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automated Quantification of the Striatal Uptake Ratio of [99mTc]-TRODAT with SPECT Imaging: Evaluation of the Diagnostic Performance in Parkinson’s Disease and the Temporal Regression of Striatal Tracer Uptake

Abstract: Purpose. We aimed at improving the existing methods for the fully automatic quantification of striatal uptake of [99mTc]-TRODAT with SPECT imaging. Procedures. A normal [99mTc]-TRODAT template was first formed based on 28 healthy controls. Images from PD patients (n = 365) and nPD subjects (28 healthy controls and 33 essential tremor patients) were spatially normalized to the normal template. We performed an inverse transform on the predefined striatal and reference volumes of interest (VOIs) and applied the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Conversely, others have found normal striatal dopaminergic integrity in ET patients with resting tremor (102). That being said, some authors reported signs of slight striatal dopaminergic degradation in classical ET (97)(98)(99)106). Of note, ET patients may show reductions of tracer uptake primarily in the caudate nucleus, contrasting the typical pattern of pronounced posterior putamenal reductions observed in PD (99,106).…”
Section: Dopaminergic Imagingmentioning
confidence: 98%
“…Conversely, others have found normal striatal dopaminergic integrity in ET patients with resting tremor (102). That being said, some authors reported signs of slight striatal dopaminergic degradation in classical ET (97)(98)(99)106). Of note, ET patients may show reductions of tracer uptake primarily in the caudate nucleus, contrasting the typical pattern of pronounced posterior putamenal reductions observed in PD (99,106).…”
Section: Dopaminergic Imagingmentioning
confidence: 98%
“…These results were similar to those found by Pagano et al [ 13 ] with 61.6 ± 9.7 for PD and by Tzen et al [ 15 ] with 70 ± 7.5 for VP. We believe that these differences in age and gender between the Parkinsonism did not influence the differences obtained in the SPECT-TRODAT results because most studies with PET-CT and SPECT have not shown statistically significant differences between changes in DAT uptake concerning sex [ 13 , 14 , 28 – 32 ]. Moreover, DAT/SPECT uptake rates in healthy patients are stable between 30 and 70 years of age, allowing someone around 70 years of age to have SPECT-TRODAT results similar to another 30-year old [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of an appropriate drug template can effectively increase the reliability and accuracy of semiquantitative data. Fang et al improved the reliability and accuracy of an automatic semiquantitative analysis [ 23 ]. They proposed a novel method that using inverse transformation of ROIs to calculate the striatal-to-reference ratio (SRR) and proved that their method has a better diagnostic performance than SPM-based method.…”
Section: Discussionmentioning
confidence: 99%